Mediating effect of customer perceived value on the relationship between service quality and customer satisfaction of e-banking in Bangladesh - Md., Abdul Bashir; Ali, Mass Hareeza; Lam, Mun Wai; Hossain, Mohammad Imtiaz; Rahaman, Md. Shumonur (Science & Engineering Research Support Society, 2020)
Purpose – The purpose of this paper is to explore the mediating role of the Customer perceived value (CPV) role between customer satisfaction (CS) and service quality (SQ) in the E- Banking sector of Bangladesh. Design/methodology/approach – A conceptual model is developed by using Theory of Planned Behaviour (TPB) to show the relationship between dependent and independent variables adopted from the existing literature. The data are collected from 323 e-banking customers taken from the four major cities of Bangladesh using structured questionnaire. Descriptive statistics including mean, standard deviation (SD), reliability, and correlation analysis are determined by using SPSS V23.0 where multi-group Confirmatory Factor Analysis method are applied by AMOS V23.0 to assess the effect of mediator variable . Findings – Results show that there is a positive relation between the SQ and CS. Similarly, SQ has positive relationship with CPV and CPV have significant positive relationship with CS. It is also found from the results that CPV partially mediate on the relationship between SQ and CS. Originality/value – The empirical evidence from this paper increase the understanding of the relationships among service quality, customer satisfaction and customer perceived value that helps the services sector especially banks to improve their service quality which leads to customer satisfaction thorough their perceived value.